Development of Interactive Learning Media Based on Digital Platforms to Improve Critical Thinking Skills in Primary School Science Education - Jimaristi Kolong; Tomi Wowe (Jurnal Penelitian Pembelajaran Fisika, 2025)
The study aims to analyze how the use of interactive learning media based on digital platforms impacts students' critical thinking skills. By collecting quantitative and qualitative data, it is hoped that comprehensive information can be obtained regarding the extent to which interactive learning media influences the development of students' critical thinking skills. The methods used are qualitative analysis: Using ADDIE analysis to identify themes and patterns that emerge from interviews and observations and quantitative analysis: Using pre-tests and post-tests to measure students' critical thinking skills before and after the use of learning media and using questionnaires to collect data on students' attitudes towards science learning using interactive media based on digital platforms. In the pre-test, only 6 of 21 students (around 29%) achieved or exceeded the KKM (65). In the post-test, all 21 students (100%) achieved the KKM. This shows a significant increase in learning outcomes after treatment/intervention using interactive media based on digital platforms.